Analysis of the Role of Garbage Bank in Improving the Community Economy in Medan Belawan District - Anggia Ramadhan; Annisa Nabila Zachra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Waste is a serious problem in Indonesia, including in Medan Belawan Regency. The Waste Bank Program is presented as a solution for waste management and community economic empowerment. This study aims to determine the role of the Waste Bank in community income. The research method used is descriptive statistics presented in the form of frequency distribution tables, histograms, steam and leaf (stem and leaf diagrams) or box plots (box line diagrams). Data collection was carried out through interviews, questionnaires and observations. The data analysis technique used is statistical analysis. The Waste Bank Program in Medan Belawan Regency has provided economic, social and environmental benefits. Economic benefits include increasing community income, creating jobs, and saving waste transportation costs. Social benefits include increasing public awareness of the importance of good waste management, and increasing public concern for the environment. Environmental benefits include reducing rubber production, reducing environmental pollution, and preserving natural resources. The Waste Bank Program in Medan Belawan Regency is one example of the application of an effective and sustainable green economy concept. This program can be a model for other waste management programs in Indonesia.